2003
DOI: 10.1002/jez.a.10222
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a direct link between stress and immunity in the mollusc Haliotis tuberculata

Abstract: Stress is thought to cause increased disease outbreaks and mortality in a number of invertebrates but currently very little information is available on mechanisms linking physiological states of stress and reduced disease resistance in these organisms. In the present study, we examined the possibility that stress alters immune functions, the principal line of defense against pathogens, in a molluscan model, the abalone Haliotis turbeculata. Immune parameters were investigated in abalones subjected to a 15 min … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
81
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(91 citation statements)
references
References 30 publications
6
81
4
Order By: Relevance
“…Several recent studies have greatly advanced our knowledge of the effect of stress on the immune response of abalone [5][6][7][8][9][10]. Malham et al [5] demonstrated that after mechanical shaking of Haliotis tuberculata, hemolymph concentrations of the stress hormones Noradrenaline and Dopamine rise, then decrease back to basal levels.…”
Section: Stress and Immunosuppression In Abalonementioning
confidence: 99%
See 2 more Smart Citations
“…Several recent studies have greatly advanced our knowledge of the effect of stress on the immune response of abalone [5][6][7][8][9][10]. Malham et al [5] demonstrated that after mechanical shaking of Haliotis tuberculata, hemolymph concentrations of the stress hormones Noradrenaline and Dopamine rise, then decrease back to basal levels.…”
Section: Stress and Immunosuppression In Abalonementioning
confidence: 99%
“…Malham et al [5] demonstrated that after mechanical shaking of Haliotis tuberculata, hemolymph concentrations of the stress hormones Noradrenaline and Dopamine rise, then decrease back to basal levels. They reported transient immune depression followed by stimulation.…”
Section: Stress and Immunosuppression In Abalonementioning
confidence: 99%
See 1 more Smart Citation
“…Further, in the clam R. philippinarum (Oubella et al 1993) and the Sydney rock oyster Saccostrea glomerata, starvation reduced hemocyte numbers and decreased phenol oxidase, peroxidase, and acid phosphatase activities (Butt et al 2007). Similarly, mechanical disturbance (shaking) reduced hemocyte abundance and oxidative burst activity in abalones Haliotis tuberculata and blue mussels Mytilus edulis (Bussell et al 2008;Malham et al 2003). In contrast, increased hemocyte numbers were observed in response to shell injury in deep-sea vent mussels Bathymodiolus azoricus (Kadar 2008) and in the Antarctic clam L. elliptica (Husmann et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a link has been established in abalone between increased stress and decreased immune functional capacity (Martello and Tjeerdema, 2001;Malham et al, 2003;Cheng et al, 2004a;2004b;2004c;2004d;2004e), leading to increased rates of bacterial infections and increased mortality (Cheng et al, 2004b;2004c;2004d;2004e). This link is based on immune function tests carried out after applying stressors such as altered salinity, shaking, decreased dissolved oxygen, increased concentrations of ammonia and nitrate and increased temperature.…”
Section: Introductionmentioning
confidence: 99%